ANALISIS EFEKTIVITAS APLIKASI MYITS THESIS MENGGUNAKAN CONFIRMATORY FACTOR ANALYSIS UNTUK PENINGKATAN LAYANAN PENYELENGGARAAN UJIAN PADA PROGRAM DOKTOR ILMU KOMPUTER - Ambarwati, Lina -; D'layla, Adifa Widyadhani Chanda; Saikhu, Ahmad (Jurusan Teknik Informatika Fakultas Teknik Universitas Trunojoyo Madura, 2024)
In the global era, Information Systems in higher education institutions are a must. Institut Teknologi Sepuluh Nopember (ITS) continuously makes efforts to develop information systems for various academic and non-academic services for the lecturer and students. One of the academic services developed at ITS is myITS Thesis application. myITS Thesis is one of the applications prepared for the management of scholars Final Project. The Computer Science Doctoral Program (PDIK) has implemented the application for examination services including qualification hearings progress, seminars, and closed dissertation hearings. This study aims to measure the effectiveness of using the myITS Thesis application in managing PDIK dissertation research services to stakeholders, especially PDIK scholars. Measurements were carried out by surveying through questionnaires with PDIK participants who used the application in the 2023/2024 academic year. The effectiveness of the application is measured through five factors, namely System Quality (KS), Information Quality(KI), System Use(PS), User Satisfaction(KP), and Individual Impact(DI). The five factors are measured through 30 Question Indicators to 55 respondents. The results of the questionnaire survey were processed using descriptive analysis and CFA modeling. CFA is used to measure validity and reliability through Standardized Loading Factor (SLF), Cronbach Alpha (CA), and Composite Reliability (CR) values. It is concluded from the modeling results based on validity and reliability measurements that the KS factor is valid with CA value=0.931 and reliable with CR value=0.73, the KI factor is valid with CA value=0.923 and reliable with CR value=0.706, the PS factor is valid with CA value=0.95 and reliable with CR value=0.734. While the KP factor is valid with CA value=0.972 and reliable with CR value= 0.814. Therefore, the myITS Thesis application has been quite effective in improving exam administration services.Keywords: questionnaire, descriptive analysis, PDIK, myITS Thesis, CFA modeling